2021
DOI: 10.3390/molecules26061786
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine Prevents Ethanol and Lipopolysaccharide-Induced Hepatic Injury in Mice

Abstract: To date, there is no effective treatment for alcoholic liver disease, despite its prevalence world-wide. Because alcohol consumption is associated with oxidative stress-induced liver injury and pro-inflammatory responses, naturally occurring antioxidants and/or anti-inflammatories may be potential therapeutics. Spermidine is an abundant, ubiquitous polyamine that has been found to display strong antioxidant and anti-inflammatory properties. To further investigate whether spermidine is an effective intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…AG treatment did not show any effect on the parameters analyzed in our experimental model. Studies from literature performed in vivo and on other cellular models showed that spermidine effectively plays a role in promoting proliferation [ 58 , 59 , 60 ] and as an antioxidant molecule [ 61 , 62 , 63 ], but our data showed that these effects are only detectable when Spd is in combination with AG.…”
Section: Discussioncontrasting
confidence: 66%
“…AG treatment did not show any effect on the parameters analyzed in our experimental model. Studies from literature performed in vivo and on other cellular models showed that spermidine effectively plays a role in promoting proliferation [ 58 , 59 , 60 ] and as an antioxidant molecule [ 61 , 62 , 63 ], but our data showed that these effects are only detectable when Spd is in combination with AG.…”
Section: Discussioncontrasting
confidence: 66%
“…When the liver is damaged, alcohol drinkers are more likely to develop fibrosis and cirrhosis [ 203 , 204 ]. Correspondingly, when rodents receive a second hit other than alcohol, liver fibrosis and cirrhosis will also appear in the liver [ 15 , 129 , 132 , 133 , 138 , 139 ]. This is also why patients with end-stage ALD usually have end-stage viral hepatitis, diabetes, and other comorbidities [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another model, ALT levels were also significantly increased after the mice were administered an LDE diet for 4 weeks, followed by one intragastric administration of ethanol (5% v / v ) and an intraperitoneal injection of LPS (2 mg/kg). Mouse liver sections also showed lipid droplet accumulation and enhanced liver damage, with distinct areas of necrosis and inflammatory cell infiltration [ 132 ]. In conclusion, the LPS plus ethanol model can induce significant lipid accumulation, inflammation, and liver damage in rodents in a short period of time [ 146 ].…”
Section: Current In Vivo Models Of Aldmentioning
confidence: 99%
“…As an antioxidant, spermidine also conferred potent anti‐inflammatory effects in the instances of liver injury, colitis, and respiratory inflammation (Adhikari et al., 2021; Liu et al., 2020; Ma et al., 2021). In a mouse model, ethanol‐ and LPS‐induced liver injuries and oxidative stresses were prevented by spermidine administration, which might be due to reductions in reactive oxygen species and lipid peroxidation by spermidine.…”
Section: Health Effects Of Dietary Spermidinementioning
confidence: 99%
“…In a mouse model, ethanol‐ and LPS‐induced liver injuries and oxidative stresses were prevented by spermidine administration, which might be due to reductions in reactive oxygen species and lipid peroxidation by spermidine. Moreover, gene expression analysis showed that spermidine inhibited the formation of proinflammatory cytokines and hepatic fibrosis (Adhikari et al., 2021). Spermidine also displayed protective effects against dextran sulfate sodium‐induced colitis in mice (Ma et al., 2021).…”
Section: Health Effects Of Dietary Spermidinementioning
confidence: 99%